PERAN BAWASLU DALAM PENYELESAIAN SENGKETA PROSES PEMILU - ALIF ANANDIKA PUTRA; ABDUL KAHAR MARANJAYA (GANEC SWARA, 2023)
The General Election (Pemilu) is a democratic party held every 5 (five) years, the Election Supervisor (Bawaslu) has an important role in electoral process disputes that occur between election participants and election participants and election organizers, as a result of the stipulation of Decisions and/or The Official Report of the KPU which is considered detrimental to the rights of election participants. Bawaslu's role is to accept process disputes, mediate the parties, if in the mediation process no agreement is found, then the Election Bawaslu carries out adjudication, Bawaslu can also correct decisions from Provincial Bawaslu and/or Regency/City Bawaslu.